2020
DOI: 10.3389/fpubh.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Selected Resistance Determinants in Diarrheal Fecal Samples Collected From Kolkata, India Reveals an Abundance of Resistance Genes and the Potential Role of the Microbiota in Its Dissemination

Abstract: study of ARG profile of diarrheal samples with varying etiologic agent revealing the presence of ARGs against the most important classes of antibiotics in the gut of diarrheal patients by common, robust molecular methods, which are easily accessible by molecular epidemiological laboratories worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 28 publications
(24 reference statements)
0
37
0
Order By: Relevance
“…Another study conducted using 1200 VC O1 isolates collected from 1995-2019 revealed that sensitivity of VC O1 El Tor strains arose in 2005 (37). Additionally, on comparison of recent reports on the antibiotic sensitivity profile of VC strains (24) with that of strains isolated a decade ago (38) it was found that a stark difference in the overall antimicrobial resistance profile exists. These findings reveal that AMR in VC is a highly dynamic phenomenon and is prone to variation and evolution with time due to different selective pressure of antibiotics (39).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Another study conducted using 1200 VC O1 isolates collected from 1995-2019 revealed that sensitivity of VC O1 El Tor strains arose in 2005 (37). Additionally, on comparison of recent reports on the antibiotic sensitivity profile of VC strains (24) with that of strains isolated a decade ago (38) it was found that a stark difference in the overall antimicrobial resistance profile exists. These findings reveal that AMR in VC is a highly dynamic phenomenon and is prone to variation and evolution with time due to different selective pressure of antibiotics (39).…”
Section: Introductionmentioning
confidence: 97%
“…Although the problem of AMR has been prevalent since the 1970s the crisis has aggravated over the years and is critical at present (15,23). At present, 100% clinical VC isolates are resistant to nalidixic acid and sulfamethoxazole-trimethoprim (24). In clinical and environmental isolates ARGs which have never been detected in VC previously thereby conferring resistance to antibiotics which worked successfully in its treatment earlier have started appearing, like, the bla NDM-1 carbapenemase encoding gene isolated in environmental and clinical strains of VC (25,26).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations